Bangladesh : Selected Issues. (IMF Staff Country Reports; Country Report, 2018)
This Selected Issues paper analyzes the performance of state-owned commercial banks (SOCB) in Bangladesh. Bangladesh's experience with the SOCBs is not unique: the SOCBs have been underperforming in comparison to private banks and foreign-owned banks. Large nonperforming loans (NPLs) imply that a large amount of the savings is being wasted by financing lossmaking activities, and therefore becomes unavailable for financing productive investments. High NPLs and the need for provisions also increase the cost of credit to good borrowers, further dampening investment and growth. Resolute steps are required to resolve the SOCBs' weak performance, reflecting empirical evidence and mixed results from the previous efforts.